Heat impacts on school sports club activities in Japan under climate change and the effectiveness of countermeasures - Takahiro Oyama; Jun’ya Takakura; Yuri Hosokawa; Yasushi Honda; Minoru Fujii; Kenichi Nakajima; Yasuaki Hijioka (Environmental Research: Health)
Millions of students in Japan participate in school sports club activities, where thousands of heat illness cases occur every year. With future climate change, there is concern about the increased health risks posed to students in sports club activities by the worsening heat environment. However, few studies have quantitatively assessed the heat illness risks associated with school sports activities and the effectiveness of countermeasures under future climate change scenarios. Here, we evaluated the impact of heat and effectiveness of countermeasures based on hourly wet-bulb globe temperature (WBGT) projections under multiple climate scenarios. For the 2060s to 2080s, even under a stringent greenhouse gas (GHG) emission control scenario (SSP1-1.9), strenuous exercise will be restricted for one to four months in five out of eight WBGT zones defined for Japan and for one to six months in six zones under the scenario with little control of GHG emissions (SSP5-8.5). In all four scenarios, unlike in the past, all physical activity should be stopped at least once a week in one or more zones. While common countermeasures like early morning exercise and reducing outdoor activity frequency effectively reduce heat illness risks, under the most pessimistic scenario (SSP5-8.5), strenuous exercise would still need to be restricted for one to four months in warmer zones, even with these measures. Common heat illness countermeasures remain necessary for sports club activities at present. However, further measures—such as replacing outdoor activities with indoor sessions—and behavioral changes—such as moving tournaments concentrated during summer vacation to cooler times of the year—will be inevitable as global warming progresses.